Structuration, fondements et objectifs de la politique linguistique au Pays Basque - Eguzki Urteaga (Lengas)
2004 marked a turning point in the linguistic policy elaborated and implemented in the Basque Country, in particular due to the transformation of the Public Authority, composed of the State, the Aquitaine Region, the Department of the Atlantic Pyrenees and the Intercommunal Syndicate for the Support of Basque Culture, into the Public Office of the Basque Language. This shows the will of the public authorities to return to a more classic scheme of local governance, with public authorities on the one hand and associative actors on the other, brought together in a Consultative Committee, and their desire to put in place a more ambitious public policy in favour of the revitalisation of the Basque language. But what about the structure, foundations and objectives of this language policy? These are the questions that this article tries to answer.